2017
DOI: 10.3390/met7070252
|View full text |Cite
|
Sign up to set email alerts
|

Mg and Its Alloys for Biomedical Applications: Exploring Corrosion and Its Interplay with Mechanical Failure

Abstract: Abstract:The future of biomaterial design will rely on temporary implant materials that degrade while tissues grow, releasing no toxic species during degradation and no residue after full regeneration of the targeted anatomic site. In this aspect, Mg and its alloys are receiving increasing attention because they allow both mechanical strength and biodegradability. Yet their use as biomedical implants is limited due to their poor corrosion resistance and the consequential mechanical integrity problems leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 162 publications
(249 reference statements)
1
48
0
2
Order By: Relevance
“…Interestingly, after processing the alloy, the yield strength is higher in compression rather than in tension [10]. Similar mechanical properties are observed in natural bones, where CYS is found to be around 130-180 MPa, TYS varied between 80 and 150 MPa, and elongation to failure is 1%-7% [3]. Thus, the proposed processing seems to be useful for the production of the next generation of biomedical materials.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, after processing the alloy, the yield strength is higher in compression rather than in tension [10]. Similar mechanical properties are observed in natural bones, where CYS is found to be around 130-180 MPa, TYS varied between 80 and 150 MPa, and elongation to failure is 1%-7% [3]. Thus, the proposed processing seems to be useful for the production of the next generation of biomedical materials.…”
Section: Introductionsupporting
confidence: 63%
“…The Mg-Zn-Ca alloys belong to the prospective metallic biomaterials due to their biocompatibility, biodegradability [1,2] and the Young's modulus of the alloys being close to that of bones [3]. A low amount of alloying elements reduces production costs, and thus increases economic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1 (Peron et al, 2017), mechanical properties of natural bone and Magnesium are indicated. With a quick review of the mechanical properties of natural bone and Magnesium, it can be concluded that the values of the material properties of natural bone and Magnesium are close to each other.…”
Section: Magnesium Against Natural Bonementioning
confidence: 99%
“…In addition, their nontoxic degradation products of Mg hydroxides can stimulate osteoblast activity and promote the regeneration of new bone . However, Mg alloys usually lose structural integrity in early implantation stage because of the poor corrosion resistance and thus fail to provide mechanical strength during the tissue repair process, which remains the main restriction for their clinical applications …”
Section: Introductionmentioning
confidence: 99%